A Theoretical and Experimental Study of a Piezoelectric Pump with Two Elastic Chambers - Xiaolong Zhao; Dingxuan Zhao; Qinghe Guo (Sensors, 2020)
The paper is a continuation of our work on the dynamic load in piezoelectric pumps. In the study, the dynamic load of liquid in the pipelines was proposed as a key factor that limits the output performance of piezoelectric pumps. To decrease the dynamic load, a piezoelectric pump with two elastic chambers was proposed in our previous published work. In this paper, the performance and key parameters of the piezoelectric pump with two elastic chambers were studied through theoretical analyses and experimental tests. After establishing the mathematical model of the piezoelectric pump with two elastic chambers, the paper theoretically analyzed the performance of the pump and the effect of different structural parameters on the performance. Then prototypes with a range of structural parameters were developed and tested. As revealed from the test results, the elastic chamber effectively decreased the dynamic load of the liquid in the pipelines and the flow rate of the prototype with two elastic chambers was higher than that of the prototype with one or no elastic chamber. However, the elastic chamber did not lead to the increase in the maximum output backpressure of the prototype. Adopting an elastic diaphragm exhibiting a smaller stiffness or a larger diameter could help decrease the dynamic load of the liquid. The elastic chamber more significantly impacted the flow rate of the piezoelectric pump with long pipelines. The pump chamber height had a significant effect on the output performance of the piezoelectric pump with two elastic chambers, which is consistent with the conventional piezoelectric pump. At the height of 0.2 mm, the flow rate of the prototype with two elastic chambers was peaked at 7.7 mL/min; at the height of 0.05 mm, the output backpressure reached the highest of 28.2 kPa. The dynamic load could decrease the amplitude of the piezoelectric vibrator, whereas the prototype with two elastic chambers could effectively reduce the impact of dynamic load on the piezoelectric vibrator. The flow rate decreased almost linearly with the backpressure. Under the same backpressure, the flow rate of the prototype with two elastic chambers was higher than that of the prototype without elastic chamber, and the flow rate difference between the two prototypes gradually decreased with the backpressure.